Integrating Technological Innovations in Teacher Professional Development: A Case Study on Enhancing Learning Outcomes - Sabariah, Sabariah; Rufi'i, Rufi'i; Nadiroh, Alvin; Lestari, Dian; Sulistiami, Sulistiami; Baidowi, Ach. (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The integration of technology in teacher training has been widely promoted to enhance learning quality, yet its effectiveness remains debated. This study investigates whether technology-assisted teacher training can significantly improve learning outcomes at SMP Negeri 1 Sukodono. Using a quasi-experimental design with a quantitative approach, the study analyzed education report scores from 2023 (pre-training) and 2024 (post-training) through paired t-tests, normality tests, homogeneity tests, and Pearson correlation analysis. Findings revealed no statistically significant improvement in average education report scores (p = 0.199), despite a 4.76% increase across five of six learning quality indicators. Strong correlations between pre- and post-training scores (r = 0.955, p = 0.003) suggest that while technology-based training has potential, its impact may require extended implementation and optimized integration for measurable improvements.